A reforma da Educação Superior no Brasil: da herança neoliberal de FHC ao legado de Lula - Ione Cristina Vieira Nunes; Lucelma Silva Braga (Desafios, 2016)
This article studies the policies to reform the Brazilian higher education implemented in the government of Fernando Henrique Cardoso (FHC) and depth in the Lula government, promoted in accordance with the policy guidelines of the World Bank. This is a bibliographic study based on major theoretical discussions on the subject and analysis of key policies of the two governments, and the agreement to the World Bank guidelines. Approaching the latest objective reality, launches hand of data available in the official bodies such as the Ministry of Education (MEC), National Institute of Educational Studies Teixeira (INEP) and the World Bank. This study highlights the commodification of higher education operated by FHC and Lula, structuring a suitable type of university capital, at this stage of its globalization.